SPECTROPHOTOMETRIC ANALYSIS OF SPIROOXAZINE AND SPIROPYRANE DYES - Đurašević, Vedran (Array, 2010)
Solvent effects are key in determining the photochromism of dye molecules in solution since exhaustion dyeing is the simplest method of applying the dye to textile substrates. In this paper, solubility and photochromic behavior of some spirooxazine and spiropyrane dyes in solutions has been investigated. It was found that polarity of the solvents influences solubility and photostability of dyes significantly. Some halochromic properties were reported as well. Effect of photochromism was investigated as a result of UV-A and UV-B irradiation wavelengths emitted by the irradiation source. Influence of solution polarity to shift in the maximum wavelength of the spectral curves has been investigated. Influence of concentration of dye to photochromic effect has been investigated and minimally demanded concentrations for the visible change to occur, caused by an UV irradiation source, were determined. PA and PES samples were dyed in different concentrations and K/S diagrams were prepared to obtain information on response time to UV irradiation and fade period a/b graphs were prepared to show differences and shiftd in hue and chromacity of the substrates dyed by photochromics.